IMPLEMENTING THINK-TALK-WRITE (TTW) STRATEGY TO IMPROVE THEUNDERSTANDING OF MATHEMATICS CONCEPTSAT SMP NEGERI 1 BANGKO - Antonius Nainggolan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
During the COVID-19 pandemic, the learning process, which was usually conducted face-to-face in front of the class, can no longer be carried out, resulting in the change of the earning system to online. This study aimed to improve students' understanding of mathematical concepts at SMP Negeri 1 Bangko through Classroom Action Research (CAR) method. Arikunto states that CAR is research conducted in the classroom with the aim of improving the quality of learning practices. The results revealed that the average score of students' understanding about the concepts before the research was 63.50 in which 13 students (42%) completed the learning objective. The average score in Cycle I was 69.83 in which 20 students (65%) completed the learning objective. Then, an increase also occurred in Cycle II, in which the average score was 81 and 31 students (100%) completed the learning objective. Thus, it could be concluded that Think Talk Write (TTW) strategy improved the students’ understanding of mathematical concepts